2016
DOI: 10.5897/ijnm2016.0208
|View full text |Cite
|
Sign up to set email alerts
|

Final year nursing students self-reported understanding of the relevance of bioscience

Abstract: Student nurses' competence in applying bioscience to practice is under-researched in South Africa. This paper reports on two objectives of a longer study: (1) to describe final year nursing students' selfreported depth of understanding of six bioscience subjects; and (2) their perceptions of relevance of the bioscience subjects to their practice using descriptions of personal critical incidents and picture interpretations of three nursing activities. A descriptive observational survey was employed using a self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 28 publications
(35 reference statements)
0
13
0
Order By: Relevance
“…While there was a high degree of alignment across the cohorts sampled regarding the factors that prompted or enhanced student disengagement (see Table 5), bioscience educators tended to believe that 'limited prior knowledge of subject area' was the strongest source of disengagement, unlike the students. This may have been linked to the educator's exposure to literature suggesting that previous science education (such as during secondary schooling) is a predictor of perceived ability to apply bioscience concepts to clinical (patient) scenarios, [10,19] as well as their direct classroom experiences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While there was a high degree of alignment across the cohorts sampled regarding the factors that prompted or enhanced student disengagement (see Table 5), bioscience educators tended to believe that 'limited prior knowledge of subject area' was the strongest source of disengagement, unlike the students. This may have been linked to the educator's exposure to literature suggesting that previous science education (such as during secondary schooling) is a predictor of perceived ability to apply bioscience concepts to clinical (patient) scenarios, [10,19] as well as their direct classroom experiences.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly challenging given the obvious import of bioscience knowledge in the development of clinical decision-making and clinical self-efficacy. [4,19,31] Educator's responses echoed much of the literature in that they felt their students did not appreciate the relevance of the bioscience courses, contributing to their lack of motivation. [9,19,20] There is, however, an apparently misalignment between student perception of lack of motivation as a contributor to disengagement (important) and relevance of the bioscience courses as a contributor to disengagement (not important).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As with many developing countries, nurses in South Africa are required to practice independently and autonomously. This is exacerbated by the fact that graduate nurses in South Africa are required to work in rural areas [ 10 ] where there is restricted access to medical doctors [ 11 ]. The Department of Health [ 12 ] reported that rural areas in South Africa contain 43.6% of the population but are assisted by only 12% of medical doctors and 19% of nurses.…”
Section: Introductionmentioning
confidence: 99%
“…The relevance of bioscience to nursing is widely acknowledged by nursing students (Fell, Dobbins, & Dee, 2016;Rafferty & Kyriacos, 2016) and academics (Birks, Ralph, Cant, Hillman, & Ylona Chun, 2015). However, there appears to be a move away from the teaching of face-to-face bioscience in nursing programmes, which is potentially detrimental to nursing practice (Fawcett, Waugh, & Smith, 2016).…”
Section: Introductionmentioning
confidence: 99%